Analýza marketingových nástrojů stavebního podniku v Kazachstánu - Shvedova, Yelizaveta (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práce je zaměřená na teoretické a praktické aspekty marketingu a marketingových strategií stavebních podniků, s důrazem na proces získávání zakázek. Cílem je analyzovat a zhodnotit účinnost těchto strategií v akviziční činnosti stavebního podniku. Teoretická část popisuje marketing a strategie v oblasti stavebnictví a proces získávání zakázek. Praktická část analyzuje marketingové nástroje stavebních firem v Kazachstánu, s ohledem na ekonomickou situaci, výběr respondentů a finanční analýzu firem. Dotazníkové šetření je prováděno na základě pěti předpokladů. Výstupem práce je navržení doporučení pro marketingovou strategii stavební firmy za účelem zvýšení její konkurenceschopnosti při soutěžení o zakázky.

The master’s thesis focuses on the theoretical and practical aspects of marketing and marketing strategies of construction companies, with an emphasis on the process of winning contracts. The aim is to analyze and evaluate the effectiveness of these strategies in the acquisition activities of a construction company. The theoretical part describes the marketing and strategies in the construction industry and the process of contract acquisition. The practical part analyzes the marketing tools of construction companies in Kazakhstan, regarding the economic situation, selection of respondents and financial analysis of the companies. The questionnaire survey is conducted based on five assumptions. The output of the thesis is the proposal of recommendations for the marketing strategy of a construction company with the aim of enhancing its competitiveness in bidding for contracts.
Analysis of marketing tools of the construction company in Kazakhstan
Keywords: stavební firma; stavební trh; marketing; digitální marketing; marketingová strategie; marketingové nástroje; komunikační mix; marketingový výzkum; construction company; construction market; marketing; digital marketing; marketing strategy; marketing tools; communication mix; marketing research